Pengaruh Struktur Modal dan Kinerja Keuangan terhadap Nilai Perusahaan pada PT Elang Mahkota Teknologi Tbk Periode 2015-2024 - Geetha Wulandari Safitri; Muhamad Nurhamdi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of capital structure and financial performance on firm value at PT Elang Mahkota Teknologi Tbk during the period 2015–2024. Capital structure is proxied by the Debt to Equity Ratio (DER), financial performance is measured by Return on Equity (ROE), and firm value is proxied by Price to Book Value (PBV). This research employs a quantitative approach with a descriptive method. The data analysis techniques used include multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that capital structure (DER) has a positive and significant effect on firm value, as indicated by a t-statistic of 3.302, which is greater than the t-table value of 2.365, with a significance level of 0.013 (< 0.05). Financial performance (ROE) also has a positive and significant effect on firm value, with a t-statistic of 2.638, exceeding the t-table value of 2.365, and a significance level of 0.034 (< 0.05). Simultaneously, DER and ROE have a significant effect on firm value, as evidenced by an F-statistic of 6.384, which is greater than the F-table value of 4.737, with a significance level of 0.026 (< 0.05). The coefficient of determination indicates that 64.6% of the variation in firm value can be explained by capital structure and financial performance, while the remaining percentage is influenced by other variables outside the research model.